ICSR DISCLOSURE, REPUTATION, VISIBILITY AND PROFITABILITY OF ISLAMIC BANK: RESEARCH WITH MEDIATOR AND MODERATOR - Habib Sa'dul Kholqi; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2021)
ABSTRAKPengungkapan ICSR menjadi isu penting yang dapat mempengaruhi reputasi dan profitabilitas bank syariah. Banyak penelitian empiris terkait pengaruh ICSR terhadap profitabilitas menunjukan hasil yang beragam. Misspesifikasi model penelitian dan strategi ICSR dapat menjadi sebab hasil tersebut. Penelitian ini bertujuan untuk menguji pengaruh pengungkapan ICSR terhadap kinerja keuangan bank syariah dengan mempertimbankan reputasi sebagai variabel mediasi dan visibilitas sebagai variabel yang memoderasi pengaruh pengungkapan ICSR terhadap reputasi. Pendekatan kuantitatif dengan metode PLS SEM digunakan untuk menguji hipotesis. 10 bank syariah di Indonesia pada periode 2014-2019 dijadikan sebagai sampel. Hasil estimasi menunjukan bahwa pengungkapan ICSR berpengaruh positif baik terhadap reputasi maupun profitabilitas. Visibilitas bank syariah juga terbukti memoderasi pengaruh pengungkapan ICSR terhadap reputasi bank. Meskipun demikian, Reputasi tidak terbukti memediasi pengaruh ICSR terhadap profitabilitas bank syariah. Implikasi dari hasil penelitian ini adala pentingnya pengungkapan ICSR bagi bank syariah karena dapat mempengaruhi reputasi dan profitabilitas perusahaan. Meskipun reputasi sendiri tidak terbukti memberikan pengaruh terhadap profitabilitas, reputasi dapat menjadi sumber daya strategis bagi bank. Selain itu, bagi bank syariah dengan visibilitas tinggi, pengungkapan ICSR menjadi sangat penting karena dampaknya yang lebih besar yang terbukti dapat memperkuat hubungan pengungkapan ICSR terhadap reputasi.Kata Kunci: Pengungkapan Islamic Corporate Social Responsibility, Variabel Mediasi, Variabel Moderasi, Profitabilitas, Bank Syariah. ABSTRACTICSR disclosure becomes an important issue that could effect reputation and profitability of Islamic Bank. a lot of empirical research on the effect of ICSR disclosure to profitability indicates an inconsistent result. Misspecification of the research model and the ICSR strategy could be the cause of it. The study aims to examine the impact of ICSR disclosure to profitability by considering reputation as a mediating variable and visibility as a variable that moderates the effect of ICSR disclosure on reputation. Quantitative approach with PLS SEM method is applied to confirm the hypothesis. 10 Indonesian Islamic Banks on 2014-2019 period are take as a sample. The estimation results show that ICSR disclosure has positive effect on reputation and profitability. It also indicates that Islamic bank visibility moderates the correlation between ICSR disclosure and reputation. However, Islamic bank reputation isn’t proven to mediate the correlation between ICSR disclosure and the profitability. The implication of the study result is that ICSR disclosure is important for the Islamic banks because it can affect its reputation and profitability. Although reputation itself is not proven to affect profitability, it can be a strategic resource for a bank. In addition, for high-visibility Islamic banks, disclosure of ICSR is crutial because of its greater impact that is proven to affect the relationship of ICSR disclosure to reputation.Keywords: Islamic Corporate Social Responsibility Disclosure, Mediating Variable, Moderating Variable, Profitability, Islamic Bank. DAFTAR PUSTAKAArdianto, E., & Sumirat, S. (2004). Dasar-dasar public relation. Bandung: Remaja Rosdakarya.Aribi, Z. A., & Arun, T. (2014). Corporate social responsibility and Islamic financial institutions (IFIs):        Management perceptions from IFIs in Bahrain. Journal of Business Ethics, 129(4), 785–794.             https://doi.org/10.1007/s10551-014-2132-9Arifin, J., & Wardani, E.A. (2016). Islamic corporate responsibility disclosure, reputasi, dan kinerja keuangan: Studi pada     bank syariah di Indonesia. Jurnal Akuntansi & Auditing Indonesia,         20(1), 38-46. https://doi.org/10.20885/jaai.vol20.iss1.art4Arshad, R., Othman, S., & Othman, R. (2012). Islamic corporate social responsibility, corporate             reputation and   performance. Journal of Economics and Management Engineering, 6(4), 643-      647. https://doi.org/10.5281/zenodo.1074857Baydoun, N., & Willett, R. (1997). Islam and accounting: Ethical issues in the presentation of financial             information. Accounting, Commerce and Finance: The Islamic Perspective, 1(1), 1-25.Bowen, F. E. (2000). Environmental Visibility: A Trigger of Green Organizational Response?. Journal        of Business Strategy and the Environtment, 9(12), 92-107. https://doi.org/10.1002/(sici)1099-            0836(200003/04)9:2<92::aid-bse230>3.0.co;2-xBranco, M. C., & Rodrigues, L. L. (2006). Communication of corporate social responsibility by            Portuguese banks: A      legitimacy theory perspective. Corporate Communications: An      International Journal, 11(3), 232-248. https://doi.org/10.1108/13563280610680821Burke, L., & Logsdon, J. M. (1996). How corporate social responsibility pays off. Long Range Planning, 29(4), 495-502. https://doi.org/10.1016/0024-6301(96)00041-6Cabral, L. (2012). Living up to expectations: Corporate reputation and sustainable competitive advantage. Working papers. New York University, 1-13.Carroll, A. B. (1979). A three-dimensional conceptual model of corporate performance. Academy of           Management Review, 4(4), 497-505. https://doi.org/10.5465/amr.1979.4498296Chambers, C. L., & Day, R. (2009). The banking sector and CSR: An unholy alliance. Financial         Regulation International, 12(9), 1-7.Crane, A., & Glozer, S. (2016). Researching corporate social responsibility communication: Themes,           opportunities and           challenges. Journal of Management Studies, 53(7), 1224-1252.             https://doi.org/10.1111/joms.12196Darmadji, T., & Fakhruddin, H. M. (2011). Pasar modal  di  Indonesia.  Jakarta:  Salemba Empat.Dendawijaya, L. (2009). Manajemen perbankan. Jakarta: Ghalia IndonesiaDonaldson, T., & Preston, L. E. (1995). The stakeholder theory of the corporation: Concepts, evidence             and implications. Academy of Management Review , 20(1), 65-91.Fama, E. F., & French, K. R. (1993). Common risk factors in the returns on stocks and bonds. Journal          of Financial Economics, 33(1), 3–56. https://doi.org/10.1016/0304-405x(93)90023-5Farag, H., Mallin, C., & Ow-Yong, K. (2014). Corporate social responsibility and financial performance          in Islamic banks. Journal of Economic Behavior and Organization, 103(July 2014), S21-S38.              https://doi.org/10.1016/j.jebo.2014.03.001Ghozali, I. G., & Latan, H. (2015). Partial least squares: Konsep, teknik dan aplikasi menggunakan   program SmartPLS 3.0. Edisi 2. Semarang: Badan Penerbit Universitas Diponegoro.Haniffa, R. (2002). Social reporting disclosure: An Islamic perspective. Indonesian Management &        Accounting Research, 1(2), 128- 146.Haniffa, R., & Hudaib, M. (2007). Exploring the ethical identity of Islamic banks via communication          in annual reports.           Journal of Business Ethics, 76(1), 97–116. https://doi.org/10.1007/s10551-006-9272-5Hansen and Mowen. (2005). Management accounting. Jakarta: Salemba Empat.Javed, M., Hussain, G., Rashid, M. A., & Ali, H. Y. (2019). The effects of corporate social responsibility    on corporate reputation and firm financial performance: Moderating role of responsible     leadership. Corporate Social Responsibility and Environmental Management, 27(3), 1395-1409. https://doi.org/10.1002/csr.1892Kementrian Agama Republik Indonesia. (2002). Al Qur’an dan terjemahannya. Jakarta: Kemenag RI.Khurshid, M. A., Al-Aali, A., Soliman, A. A. and Amin, S. M. (2014). Developing an Islamic corporate            social responsibility model (ICSR). Competitiveness Review, 24(4), 258-274. https://doi.org/10.1108/CR-01-2013-0004Laplume, A. O., Sonpar, K., & Litz, R. A. (2008). Stakeholder theory: Reviewing a theory that moves   us. Journal of Management, 34(6), 1152-1189. https://doi.org/10.1177/014920630 8324322Maignan, I., & Ferrell O. C. (2004). Corporate social responsibility and marketing: An integrative          framework. Journal of   the Academy of Marketing Science, 32(1), 3-19. https://doi.org/10.1177/0092070303258971McWilliams, A., & Siegel, D. (2000). Corporate social responsibility and financial performance: Correlation or misspecification. Strategic Management Journal, 21(5), 603-609. https://doi.org/10.1002/(SICI)1097-0266(200005)21McWilliams, A., Siegel, D. S., & Wright, P. M. (2006). Corporate social responsibility: strategic implications. Journal of Management Studies, 43(1), 1-18. https://doi.org/10.1111/j.1467- 6486.2006.00580.xMenne, F., Winata, L., & Hossain, M. (2016). The influence of CSR practices on financial performance:          Evidence from Islamic financial institutions in Indonesia. Journal of Modern Accounting and Auditing, 12(2), 77-90. https://doi.org/10.17265/1548-6583/2016.02.002Nugraheni, P., & Erlinda, N. K. (2019). Implementation of the AAOIFI index on CSR disclosure in     Indonesian Islamic Banks. Journal of Financial Reporting and Accounting, 17(3), 365-382. https://doi.org/10.1108/JFRA-02-2018-0013Park, S. (2017). Corporate social responsibility, visibility, reputation and financial performance:   empirical analysis on the moderating and mediating variables from korea. Social   Responsibility Journal, 13(4), 856-871. https://doi.org/10.1108/SRJ-01-2017-0012Parmar, B. L., Freeman, R. E., Harrison, J. S., Wicks, A. C., Purnell, L., & De Colle, S. (2010).            Stakeholder theory: The state of the art. The Academy of Management Annals, 4(1), 403–       445. https://doi.org/10.1080/19416520.2010.495581Patten, D. M. (2019). Seeking legitimacy. Sustainability Accounting, Management and Policy Journal, 11(6), 1009-1021. https://doi.org/10.1108/sampj-12-2018-0332Platonova, E., Asutay M., Dixon R., & Mohammad S. (2018). The impact of corporate social             responsibility disclosure on financial performance: Evidence from the GCC Islamic     banking sector. Journal Business Ethic, 151, 451-471. https://doi.org/10.1007/s10551-016-3229-0Rehman, Z. R., Zahid, M., Rahman, H. U., Asif, M., Alharthi, M., Irfan, M., & Glowacz, A. (2020). Do corporate social responsibility disclosures improve financial performance? A perspective of the Islamic banking industry in Pakistan. Sustainability, 12(8), 1-18. https://doi.org/10.3390/su12083302Riyanto, B. (2013). Analisis Laporan Keuangan. Yogyakarta: BPFERose, C. & Thomsen, S. (2004). The impact of corporate reputation on performance: some Danish         evidence. European Management Journal, 22(2), 201-210. https://doi.org/10.1016 /j.emj.2004.01.012Saeidi, S. P., Sofian, S., Saeidi, P., Saeidi S. P., & Saaeidi, S. A. (2015). How does corporate social     responsibility contribute to firm financial performance? The mediating role of competitive advantage, reputation and customer satisfaction.      Journal of Business Research, 68, 341-450. https://doi.org/10.1016/j.jbusres.2014.06.024Saha, A. K. (2019). Relationship between corporate social responsibility performnce and disclosure:        Commercial bank of Bangladesh. Social Responsibility Journal, 15(4), 451-468. https://doi.org/10.1108/SRJ-07-2017-0137Sawitri, D. R., Juanda A., & Jati A. W. (2017). Analisis pengungkapan corporate sosial responsibility    berdasarkan Islamic social reporting index. Jurnal Ilmiah Akuntansi, 15(2), 139-149. https://doi.org/10.22219/jrak.v7i1.12Scholtens, B. (2009). Corporate social responsibilty in the international banking industry. Journal of       Business Ethics, 86(2), 159-175. https://doi.org/10.1007/sl0551-008-9841-xSugiyono. (2013). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta.Suhadak, Kurniaty, Handayani, S.R., & Rahayu, S. M. (2019). Stock return and financial performance as      moderation variable in   influence of good corporate governance towards corporate value.   Asian Journal of Accounting Research, 4(1), 18-          34. https://doi.org/10.1108/AJAR-07-2018-0021Sunaryo,  B. A., & Mahfud, M. K. (2016). Pengaruh size, profitabilitas leverage dan umur terhadap       pengungkapan tanggung jawab sosial perusahaan. Diponegoro Journal of           Management, 5(2), 1-14.Udayasankar K. (2008). Corporate social responsibility and firm size. Journal of Business Ethics, 83(2),           167–175. https://doi.org/10.1007/s10551-007-9609-8Vanstraelen, A., Zarzeski, M. T., & Robb, S. W. G. (2003). Corporate nonfinancial disclosure practices            and financial analyst forecast ability across three European countries. Journal of International Financial Management and Accounting, 14(3), 250-278. https://doi.org/10.1111/1467-646X.00098Wardayati, S.M. Implikasi shariah governance terhadap reputasi dan kepercayaan bank syariah.          Walisongo: Jurnal Penelitian Sosial-Keagamaan, 19(1), 1-24.Wilmshurst, T. D., & Frost, G. R. (2000). Corporate environmental reporting. Accounting, Auditing & Accountability Journal, 13(1), 10–26. https://doi.org/10.1108/09513570010316126Yu Lu, Cahan, S., & Ma, D. (2019). Is CSR performance related to disclosure tone in earnings             announcements. Accounting Research Journal, 32(2), 129-147. https://doi.org/10.1108/ARJ-05-2016-0059Yu, J., Lo, C. W-H., & Li P. H. Y. (2016). Organizational visibility, stakeholder environmental pressure        and corporate environmental responsiveness in China. Business Strategy and the Environmental, 26(3), 371-384. https://doi.org/10.1002/bse.1923Zafar, M. B., & Sulaiman, A. A. (2019). CSR narrative under Islamic banking paradigm. Social           Responsibility Jurnal, 17(1), 15-29. https://doi.org/10.1108/SRJ-09-2018-0230